WTO dispute settlement cases involving the agreement on agriculture, 1995–2019 - Glauber, Joseph W.; Xing, Xiaorong (International Food Policy Research Institute, 2020)
A landmark achievement of the Uruguay Round, and notably, the Agreement on Agriculture, was the full inclusion of agriculture in multilateral rules and disciplines. Since the birth of World Trade Organization (WTO), a significant number of member countries have used the dispute settlement mechanism (DSM) for resolving the disputes in agriculture. The DSM has played an important role not only for those parties involved in the disputes, but also by helping member countries to better understand the WTO rules, and therefore help guide them in developing domestic policies and trade policies that are consistent with WTO requirements. This paper examines trade disputes involving the Agreement on Agriculture since the WTO was formed in 1995 through December 2019. It analyzes who brought the disputes and against whom disputes were brought, and provides details on the natures of the disputes, the duration of disputes, and, the outcome of those disputes.